Permainan Edukatif Flashcard Meningkatkan Pengetahuan Anak tentang Kesehatan Gigi - Rohmah, Atika; Latifah Susilowati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Dental health issues are commonly found among school-aged children. These issues can cause pain and discomfort, affecting dental function and leading to difficulties in eating, which in turn impacts nutritional intake. Efforts to improve dental health can be implemented through educational games. Educational tools are equipment used by children for play or games aimed at enhancing their skills, one of which is flashcards. Flashcards are cards with two sides, where the front side displays an image, and the back side contains a description of the image. Objective: To determine the effect of educational flashcard games on children's knowledge of dental health at Noyosutan Elementary School. Method: A pre-experimental design with a one-group pretest-posttest design was used. The study involved 36 respondents, using a questionnaire on dental health knowledge as the instrument and flashcards containing images related to dental health as the educational game. Result: The study showed a significant difference in knowledge before and after playing the educational flashcard game, with a p-value of 0.000 (p <0.005). The educational flashcard game had a significant effect on children’s knowledge of dental health. Conclusion: Children's knowledge of dental health improved after engaging in the educational game using flashcards.